Glacial Outburst Floods Responsible for Major Environmental Shift in Arctic Coastal Catchment, Rekvedbukta, Albert I Land, Svalbard - Aleksandra Wołoszyn; Zofia Owczarek; Iwo Wieczorek; Marek Kasprzak; Mateusz C. Strzelecki (Remote Sensing, 2022)
Small Arctic coastal catchments and coastal lagoon systems are some of the most vulnerable to climate change. Glacial retreat and the development of glacial lakes and drainage systems provide opportunities for hazardous events such as GLOFs. We observe that the stability of lagoons and their associated barriers are controlled by the frequency and magnitude of storms approaching the coasts, access to sediment supplies and resilience to sea-level rise. Based on multidecadal remote sensing data, we were able to identify the rate of glacial recession, the development of glacial lakes, vegetation response to climate change and a GLOF event, and shoreline and lagoon responses to the environmental shifts within the small catchment. Here we present an example of lagoon system evolution where a glacial outburst flood exerted significant control over lagoon drainage and coastal barrier stability.